A zinc–iron redox-flow battery under $100 per kW h of system capital cost. Issue 10 (18th September 2015) - Gong, Ke; Ma, Xiaoya; Conforti, Kameron M.; Kuttler, Kevin J.; Grunewald, Jonathan B.; Yeager, Kelsey L.; Bazant, Martin Z.; Gu, Shuang; Yan, Yushan
Abstract : A zinc–iron redox-flow battery is developed that uses low cost redox materials and delivers high cell performance, consequently achieving an unprecedentedly low system capital cost under $100 per kW h. Abstract : Redox flow batteries (RFBs) are one of the most promising scalable electricity-storage systems to address the intermittency issues of renewable energy sources such as wind and solar. The prerequisite for RFBs to be economically viable and widely employed is their low cost. Here we present a new zinc–iron (Zn–Fe) RFB based on double-membrane triple-electrolyte design that is estimated to have under $100 per kW h system capital cost. Such a low cost is achieved by a combination of inexpensive redox materials ( i.e., zinc and iron) and high cell performance ( e.g., 676 mW cm −2 power density). Engineering of the cell structure is found to be critical to enable the high power density. Our cost model shows that a Zn–Fe RFB demonstrates the lowest cost among some notable RFBs and could reach the 2023 cost target set by the U.S. Department of Energy ($150 per kW h).